Pengaruh Upah Minimum Regional, Investasi, Dan Pertumbuhan Ekonomi Terhadap Pengangguran Terbuka Di Kota Mataram Tahun 2008-2022 - Saputra, Rizal; Salmah, Emi; Sujadi, Sujadi (Universitas Mataram, 2024)
This research aims to analyze the influence of regional minimum wages, investment, and economic growth partially and simultaneously on the level of open unemployment in Mataram City. The type of research used in this research is an associative quantitative method. This research uses secondary data in the form of a time series published by the Central Statistics Agency and related agencies in Mataram City for the period 2008-2022. The data that was obtained was then carried out with a multiple regression test using SPSS version 25 software. The results of the analysis show that the independent variables in this research can explain the open unemployment variable in Mataram City of 87 percent, while 13 percent is influenced by other variables outside this research. Partially, the regional minimum wage and economic growth variables have a significant negative effect on the open unemployment rate, while the investment variable has a significant positive effect on the Mataram City unemployment rate. Meanwhile, regional minimum wage variables, investment, and economic growth simultaneously influence the open unemployment rate in Mataram City.